2021
DOI: 10.1111/srt.13025
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental evaluation of skin barrier function and clinical outcomes during dupilumab treatment for atopic dermatitis: An observational study

Abstract: Atopic dermatitis (AD) is a chronic, recurrent, inflammatory skin disease characterized by pruritus, xerosis, and skin barrier dysfunction. It is most commonly observed in pediatric populations, although it can persist or develop in adults. Its pathogenesis is both multifactorial and environmental where genetic and immunologic factors can play a crucial role. Atopic dermatitis has a significant social and psychological impact on the people affected, with a reduction in the quality of life. In atopic dermatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…A study similar to ours has already been performed in a cohort of 30 AD patients treated with dupilumab, showing that there was an inverse proportional correlation between TEWL and disease severity after 8 weeks of dupilumab treatment. 28 Moreover, Rohner et al 29 demonstrated in 10 AD patients that dupilumab led to a significant increased expression of epithelial barrier proteins [filaggrin, lymphoepithelial-Kazal-type-related inhibitor (LEKTI), human β-defensin-3 and cathelicidin LL-37]. Similar conclusions were drawn by Guttman-Yassky et al , 20 who found increased expression of the epidermal differentiation, barrier and lipid metabolism genes filaggrin, loricrin, claudins and ELOVL3.…”
Section: Discussionmentioning
confidence: 70%
“…A study similar to ours has already been performed in a cohort of 30 AD patients treated with dupilumab, showing that there was an inverse proportional correlation between TEWL and disease severity after 8 weeks of dupilumab treatment. 28 Moreover, Rohner et al 29 demonstrated in 10 AD patients that dupilumab led to a significant increased expression of epithelial barrier proteins [filaggrin, lymphoepithelial-Kazal-type-related inhibitor (LEKTI), human β-defensin-3 and cathelicidin LL-37]. Similar conclusions were drawn by Guttman-Yassky et al , 20 who found increased expression of the epidermal differentiation, barrier and lipid metabolism genes filaggrin, loricrin, claudins and ELOVL3.…”
Section: Discussionmentioning
confidence: 70%
“…Empty Hy and Rm (bare R. mucosa ) showed moderate therapeutic effects, while Hy@Rm alleviated AD symptoms much more effectively. In AD patients, skin barrier destruction is associated with the increase of trans-epidermal water loss (TEWL), and the reduction of skin hydration/elasticity [ 56 ]. Regarding these indicators of skin conditions, there appeared an evident improvement of skin status, as evidenced by the remarkably reduced TEWL ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that dupilumab decreases TEWL and increases SCH, reflecting skin barrier recovery. The lack of differences in SCH in other studies may be explained by the shorter follow-up [ 46 ] or the limited number of participants [ 47 ]. Moreover, we also found that dupilumab decreases temperature, which might be reflecting a reduction in the inflammatory load, while we did not find changes in pH.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have also evaluated the impact of dupilumab on skin barrier function [ 46 , 47 , 48 , 49 , 50 ]. They showed that dupilumab reduced TEWL on non-involved and involved skin [ 46 , 47 , 48 , 49 , 50 ]. The impact of dupilumab in SCH differs between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation